2023
DOI: 10.2147/opth.s425709
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Durability of Brolucizumab: An 8-Month Post-Marketing Surveillance Analysis

Nicholas Saba,
Scott Walter

Abstract: Importance Brolucizumab (Beovu ® ) is an anti-vascular endothelial growth factor (anti-VEGF) agent approved for the treatment of neovascular age-related macular degeneration (nvAMD). Brolucizumab was marketed for its noninferiority to aflibercept and its potential for greater durability. However, post-marketing utilization has been tempered by safety concerns. Objective We evaluate the visual and anatomic efficacy of brolucizumab, examine chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the HAWK and HARRIER studies, however, the brolucizumab injection group had a significantly higher incidence of IOI at 4.7%, compared to the aflibercept group which had a much lower rate of 0.6% [ 4 ]. Similarly, Saba et al reported that the incidence of IOI was comparable at 4.8% in the 8-month post-marketing surveillance analysis [ 7 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the HAWK and HARRIER studies, however, the brolucizumab injection group had a significantly higher incidence of IOI at 4.7%, compared to the aflibercept group which had a much lower rate of 0.6% [ 4 ]. Similarly, Saba et al reported that the incidence of IOI was comparable at 4.8% in the 8-month post-marketing surveillance analysis [ 7 ].…”
Section: Discussionmentioning
confidence: 97%
“…Visual prognosis of most patients who underwent IOI revealed relatively good during the follow-up period [ 4 ]. However, there were several cases with relatively poor visual prognosis, such as retinal vasculitis with RAO [ 4 , 7 9 ]. A retrospective analysis of 26 eyes from 25 patients evaluated retinal vasculitis following the administration of brolucizumab, and 92% of cases of retinal vasculitis were accompanied by anterior chamber inflammation and/or posterior segment inflammation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in fact, many studies in clinical ophthalmology focus only on the eye instead of a person with paired organs. For example, Saba and Walter [20] worked on a retrospective consecutive case series of 626 eyes (543 patients) with nvAMD treated with 1438 Brolucizumab injections. Some of these patients contributed one eye and some contributed two eyes, and it would be imprudent to ignore the correlation between two eyes from the same patient in a statistical analysis.…”
Section: Discussionmentioning
confidence: 99%